2018
DOI: 10.3389/frobt.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Resisting Influence: How the Strength of Predispositions to Resist Control Can Change Strategies for Optimal Opinion Control in the Voter Model

Abstract: In this paper, we investigate influence maximization, or optimal opinion control, in a modified version of the two-state voter dynamics in which a native state and a controlled or influenced state are accounted for. We include agent predispositions to resist influence in the form of a probability q with which agents spontaneously switch back to the native state when in the controlled state. We argue that in contrast to the original voter model, optimal control in this setting depends on q: For low strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Such a scenario may be appropriate when there is an effect of lock-in, e.g., if agents make one-off decisions about buying an expensive product or generally making decisions when further change is costly. However, as it has been realized by some authors [9,25,29,43], these models may not be appropriate in situations in which agents are subject to various sources of social influence, and decisions can be changed over time. Such decision making can be described by various types of dynamic models of opinion formation for which there is a rich interdisciplinary literature (see, c The author 2018.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a scenario may be appropriate when there is an effect of lock-in, e.g., if agents make one-off decisions about buying an expensive product or generally making decisions when further change is costly. However, as it has been realized by some authors [9,25,29,43], these models may not be appropriate in situations in which agents are subject to various sources of social influence, and decisions can be changed over time. Such decision making can be described by various types of dynamic models of opinion formation for which there is a rich interdisciplinary literature (see, c The author 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas most modeling effort has been devoted to understanding various facets of opinion dynamics, some recent studies have also started to consider influence maximization for such dynamic models of opinion formation. In this context, previous work has focused on exploring optimal control allocations that maximize influence in the stationary state of the kinetic Ising model [26][27][28], for the AB model [2] and for the voter dynamics [9,25,29,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has started to address questions of optimal allocation for the dynamic models of opinion formation, with studies focusing on the voter dynamics [37][38][39][40][41], Ising-like models [42], and variants of AB models [43]. While some studies point to a nuanced picture of optimal allocations depending on noise and details of the goal-functions of the optimizing parties [40,44], a common thread is that optimal allocations are often well approximated by targeting hub nodes [37,39].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, [22,24,25] have pointed out that heuristics targeting hub nodes perform very well on undirected heterogeneous networks, even though heuristics based on centrality metrics do not correspond to exactly optimal allocations for all types of networks [22]. This picture has been qualified by some of our recent work which has shown that targeting hub nodes is not necessarily optimal in all situations, e.g., not if agents have a large propensity to resist influence [35] or if time horizons of the influence maximizer are very short [36].…”
Section: Introductionmentioning
confidence: 99%